Clinical Use of Atrial Pacing Test in Angina Pectoris. Issue 5610 (13th July 1968) - Balcon, Raphael; Maloy, William C.; Sowton, Edgar
Abstract : Atrial pacing can be used as a safe test in the assessment of patients with angina pectoris. The results are useful in clinical judgements, and this method of investigation may be indicated for patients in whom the diagnosis of angina pectoris is in doubt or who are being considered for surgical treatment of ischaemic heart disease.